Our Assessment Using Palate Postoperative Problems Score (PPOPS): Tool for the Evaluation of Results in Palatal Surgery Techniques - Modica, Domenico Michele (Indian J Otolaryngol Head Neck Surg, 2018)
Obstructive sleep apnoea syndrome is a chronic condition characterized by frequent episodes of collapse of upper airways during sleep. Prevalence of the disease is settled at about 3–7%. Today, palatal surgery is a reference point in OSAHS treatment and there are many different surgical techniques. The purpose of our work is to compare post-operative results of palate surgery techniques used in our practice in OSAHS patients, studying the degree of patients’ satisfaction with a recent score recommended by Rashwan et al. called PPOPS (Palate Post-Operative Problems Score). A retrospective study was performed on a sample of 40 patients subject to different palate surgery techniques for OSAS. Analysed surgical techniques were: Expansion Sphincter Pharyngoplasty (ESP), Uvulopalatopharyngoplasty (UPPP), Anterior Pharyngoplasty (AP), Barbed Reposition Pharyngoplasty (BRP). Patients answered the PPOPS and the results for each of the four techniques were compared. Group differences in the questionnaire total score were evaluated through Tukey’s honest significance test for multiple (pairwise) comparisons. Overall average scores in the four groups were: AP 2.21, ESP 5.92, UPPP 2.8 and BRP 2.4. Comparing ESP with the other techniques (BRP, AP and UPPP) the scores were significantly higher (P < 0.05). Pairwise comparisons between the other three techniques (FA, UPPP and BRP) had a P value higher than 0.05, allowing to state that questionnaire results, in these cases, were similar to each other. Our work shows that different surgical techniques, even with the same purpose, could have different characteristics during follow-up. PPOPS is useful in post-operative for a better surgical practice.